ANALISIS PRODUKSI DAN PENDAPATAN HASIL TANGKAP NELAYAN DI DESA MUARA GADING MAS KECAMATAN LABUHAN MARINGGAI LAMPUNG TIMUR - Eny Ivan's; Istiana Istiana; Endang Sri Utami (Jurnal TROFISH, 2023)
This study aims to analyze aspects of production and income aspects of fishermen’s in Muara Gading Mas Village, Labuhan Maringgai District, East Lampung. The sampling technique was carried out by census with a total of 27 skipper fishermen. The data analysis method used is descriptive qualitative and quantitative descriptive analysis. The results of the study show that technically the production aspects of fishing activities at the research location are closely related to the variables of length of work, length of time at sea, type of vessel, type of fishing gear and catchment area. As for the income aspect, the amount of income for skipper fishermen from the catch is Rp. 2,462,304.- in one fishing activity while for Ship's Crews (ABK) it is only Rp. 615,576.-. When compared to the UMR in East Lampung Regency, the income value of fishermen is still relatively low. Therefore, in order to improve the welfare of fishermen, it is hoped that the government's participation will be more intensive by providing assistance programs that can empower communities to become more developed and developing, for example through developing home industries, lending business capital and providing alternative employment opportunities. outside the fisheries sector.